TALABALARDA PEDAGOGIK KASBIY IDENTLIKNI SHAKLLANISH BOSQICHLARI - Qurbonova, F.M. (SCIENCE and SOCIETY, 2025)
This article is devoted to scientific and practical research on the relationship between participants and the educational sphere for the development of students’ professional identity in higher educational institutions. The role of the social environment and pedagogical and psychological characteristics in professional development of students is discussed. Information is provided on methods for developing pedagogical professional identity in students.